The Effect of Applying Liquid Organic Fertilizer Kasgot on the Growth and Weight of Kolesom Leaf Consumption (Talinum triangulare [Jacq.] Willd) - Nur Fitria, Anisa; R. Eviyati; Amini, Zakiyah (Ann Publisher, 2023)
The purpose of the research was to determine the effect of kasgot liquid organic fertilizer on the growth and consumption weight of kolesom leaves (Talinum triangulare [Jacq.] Willd). The experiment was conducted in Babakan Jawa Village, Majalengka District, Majalengka Regency, from August to October. The land used for research has a clay texture. Rainfall at the research location is included in type C, which is rather wet. The research method used was a Randomized Complete Design (RCD). The treatment consisted of one factor with four replications. The factor in this study is the concentration of kasgot liquid organic fertilizer which consists of six treatment levels, namely: K1 (control/no treatment), K2 (5 ml l-1), K3 (10 ml l-1), K4 (15 ml l-1), K5 (20 ml l-1), K6 (25 ml l-1) all treatment were repeated 4 replication. Variables observed were plant height (cm), number of leaves (strands), stem diameter (mm), number of shoots per plant of upright leaves (strands), shoot weight per plant (g), total shoot weight (g). The results showed that the application of kasgot liquid organic fertilizer had a significant effect on the growth of kolesom plants, namely on the diameter of the stem at the age of 6 MSPT and the number of leaves at the age of 7 MSPT. The application of liquid organic fertilizer Kasgot K2 5 ml l-1 gave the best results on the diameter of the stem at the age of 6 MSPT and 5 20 ml l-1 gave the best results on the number of leaves at the age of 7 MSPT.